Mahmud Yunus's Educational Thoughts in Teaching Arabic: Analysis of Rational, Practical and Emotional Approaches - Runtoni (Indra institute Research & Publication, 2024)
The main aim of this research is to study and research the thoughts of reformer figures such as Mahmud Yunus. In this research the author focuses on the Arabic language learning approach used by Mahmud Yunus. This research is important because apart from Mahmud Yunus being a pioneer, he also laid the foundation for the Arabic language learning approach in Indonesia. The research method is completely carried out in the form of library research with the data analysis technique used is content analysis. The research results show that in teaching Arabic, Mahmud Yunus in his thinking applies three approaches, namely: a) rational approach, b) practical approach, and c) emotional approach. A rational approach is applied by emphasizing the depth of the material to bring students to critical thinking so that students can use their ratios as fully as possible. A practical approach is applied by placing emphasis on developing as much as possible the student's skills. So that apart from being critical and intelligent, students can also apply their knowledge to society. The emotional approach is applied by emphasizing how teachers are able to instill morals in students by providing good role models.